Teledermatology: Canadian dermatologists’ practice patterns, perceived challenges and future recommendations - Sidra Sarfaraz; Tarek Turk; Samuel A. J. Lowe; Luvneet Verma; Marlene Dytoc (Dermatology Reports)
The use of teledermatology has increased significantly in recent years. The objective of this study was to determine Canadian dermatologists’ and dermatology residents’ perspectives on teledermatology. An online survey was created to determine participants’ teledermatology practice patterns and their perception of the challenges, education, training, and research in teledermatology. The survey was distributed through the Canadian Dermatology Association and by administrative staff at Canadian Dermatology departments. There were 33 respondents: 66.7% of respondents started using teledermatology during the COVID-19 pandemic, and 93.8% reported that teledermatology accounted for 0-25% of their practice. Convenience, access, and safety were identified as the primary advantages of teledermatology. Teledermatology was mainly utilized for medication monitoring or refills and to assess, manage, or follow up on dermatitis, other chronic inflammatory conditions, and pre-diagnosed dermatologic conditions. Poor photo quality (32.3%) and the inability to conduct physical examinations or accurately diagnose conditions (74.2%) were reported as significant challenges. Respondents recommended education on the medicolegal considerations of teledermatology and research on how teledermatology compares to in-person consultations. Overall, teledermatology offers convenience, access, and improved safety for patients and healthcare professionals. However, addressing challenges related to physical examinations, accurate diagnoses, and photo quality is essential for optimal care delivery.